Pengaruh Konten YouTube Mengenai Kualitas Informasi terhadap Keputusan Pembelian - Natalie, Fiesca; Junaidi, Ahmad (Kiwari, 2024)
The main goal of this research is to examine the influence of David Gadgetin's YouTube content on the quality of information affecting customers' decisions to buy gadgets. The theoretical foundation for this study is grounded in the Uses and Gratification theory. The research adopts a quantitative methodology, employing a questionnaire as the primary tool for collecting data. The sampling method is determined through the Slovin formula, considering a known population. The research population consists of subscribers to David Gadgetin's YouTube channel, totaling 100 respondents. Data analysis involves various techniques such as Validity test, reliability test, classical hypothesis test, multiple linear regression test, T test, F test, correlation coefficient test (R) and coefficient of determination test (R2). Data were processed using SPSS version 23.0. Results indicate that the R value (correlation value) contributes to 80% of the influence of YouTube content, with the quality of information playing a significant role in purchasing decisions. Hypothesis testing (T-test) reveals that the calculated T1 is -30.484, exceeding the table T1 of 1.984, leading to the acceptance of Ha and rejection of Ho. Similarly, the calculated T2 is 12.203, surpassing the table T2 of 1.984, indicating the acceptance of Ha and rejection of Ho. Therefore, it can be concluded that there is a discernible influence between the quality of content and information on YouTube GadgetIn concerning customers' purchasing decisions. Penelitian ini bertujuan untuk mengevaluasi dampak konten YouTube yang dibuat oleh David Gadgetin terhadap kualitas informasi dan bagaimana hal tersebut memengaruhi keputusan pembelian pelanggan, khususnya dalam konteks perangkat gadget. Teori menjadi landasan dalam penelitian ini adalah Teori Kegunaan dan Gratifikasi. Metode penelitian yang diterapkan adalah kuantitatif, dengan menggunakan kuesioner sebagai alat pengumpulan data. Pengambilan sampel dilakukan menggunakan rumus Slovin dengan jumlah populasi sebanyak 100 responden yang merupakan pelanggan langganan YouTube David Gadgetin. Analisis data melibatkan Uji Validitas, Uji Reliabilitas, Uji Hipotesis Klasik, Uji Regresi Linier Berganda, Uji T, Uji F, Uji Koefisien Korelasi (R), uji koefisien determinasi (R2) dengan pengolahan data menggunakan perangkat lunak SPSS versi 23.0. Hasil penelitian menunjukkan bahwa angka R (korelasi) memberikan kontribusi sebesar 80% terhadap pengaruh konten YouTube terhadap kualitas informasi yang pada gilirannya memengaruhi keputusan pembelian. Melalui uji hipotesis (Uji T), dapat disimpulkan bahwa angka T1 sebesar -30,484 > T1 tabel 1,984, menunjukkan penerimaan Ha dan penolakan Ho, serta angka T2 sebesar 12,203 > T2 tabel 1,984, yang juga menunjukkan penerimaan Ha dan penolakan Ho. Dengan demikian, disimpulkan bahwa terdapat hubungan antara kualitas konten dan informasi YouTube GadgetIn dengan keputusan pembelian pelanggan GadgetIn.